An ECG-based Secret Data Sharing scheme supporting emergency treatment of Implantable Medical Devices - Guanglou Zheng; Gengfa Fang; Shankaran, Rajan; Orgun, Mehmet A.; Dutkiewicz, Eryk (WPMC : 2014 International Symposium on Wireless Personal Multimedia Communications : 7-10 September 2014, Sydney, Australia, 2014)
The security issue of wireless Implantable Medical Devices (IMD) is an emerging area of research. The unique challenge here is that an IMD should be accessed by doctors with no authorization for emergency treatments while it still has to be protected from adversaries. In this paper, we propose a novel ECG-based Secret Data Sharing (ESDS) scheme in order to protect the IMD data privacy against eavesdropping and other active attacks from adversaries. The scheme establishes a secure wireless channel wherein the secret is encrypted with a random ECG bit string generated from real-time ECG signals. This secret can only be revealed by an IMD programmer which has the ability of measuring real-time ECG signals synchronously with the IMD. Since there is no pre-deployment of credentials, the IMD can be accessed by doctors without prior authorization. Performance analysis based on the real ECG data shows that the encrypted secret cannot be revealed by non-real-time or other patients' ECG signals; thus, it achieves our design goal of providing robust security.